Ḥaqq o bā̤til kī kasauṭī : maẕhab-i ḥaqqah Ahlisunnat par dalāʼil be naẓīr . - Nūrī, Iqbāl Aḥmad (Ri̤zvī Kutab Ḵẖānah, 1962)
On the basic differences between the Bareilly and Deoband schools of Islamic theology.